Multicomponent Synthesis of Unsaturated γ-Lactam Derivatives. Applications as Antiproliferative Agents through the Bioisosterism Approach: Carbonyl vs. Phosphoryl Group - Xabier del Corte; Adrián López-Francés; Ilia Villate-Beitia; Myriam Sainz-Ramos; Edorta Martínez de Marigorta; Francisco Palacios; Concepción Alonso; Jesús M. de los Santos; José Luis Pedraz; Javier Vicario (MDPI AG, 2022)
We report efficient synthetic methodologies for the preparation of 3-amino and 3-hydroxy 3-pyrrolin-2-ones (unsaturated γ-lactams) through a multicomponent reaction of amines, aldehydes and acetylene or pyruvate derivatives. The densely substituted γ-lactam substrates show in vitro cytotoxicity, inhibiting the growth of the carcinoma human tumor cell lines RKO (human colon epithelial carcinoma), SKOV3 (human ovarian carcinoma) and A549 (carcinomic human alveolar basal epithelial cell). In view of the possibilities for the diversity of the substituents that offer a multicomponent, synthetic methodology, an extensive structure-activity profile is presented. In addition, the bioisosteric replacement of the flat ester group by a tetrahedral phosphonate or phosphine oxide moiety in γ-lactam substrates leads to increased growth inhibition activity. Cell morphology analysis and flow cytometry assays indicate that the main pathway by which our compounds induce cytotoxicity is based on the activation of the intracellular apoptotic mechanism.